The Versatility of Temporalis Muscle Flap in Reconstruction of Maxillofacial Region - Harsono, Anastasia Dessy; Kreshanti, Prasetyanugraheni; Handayani, Siti; Bangun, Kristaninta (Lingkar Studi Bedah Plastik Foundation, 2013)
Background: The temporalis muscle !ap (TMF) is a very versatile and valuable axial flap, which could be used in various reconstructive procedures in and around the maxillofacial region. The surgical anatomy, vascular pattern and technique of elevation of the flap are described, associated with our experience in different reconstructive situations. Patient and Method: There were two patients, one case of TMJ ankylosis and one case of facial paralysis. The TMF was used as an interpositional arthroplasty for TMJ ankylosis, as a dynamic facial reanimation for facial paralysis. Result: In the first patient, he was able to open his mouth 4 cm in 2 weeks following the surgery. There was no pain or other complication complained. In second patient, in two weeks follow up after the surgery, we found the edema was decrease gradually. The contraction on the right nasolabial sulcus was slightly seen. Summary: These report described the reliability, versatility and reproducibility of temporalis muscle flap. The rich vascularized tissue and its proximity to the reconstruction site make this flap reliable. TMF should be taken into consideration before deciding on more extensive reconstructive procedures.